Understanding the basis of fatigue in children with unilateral hearing loss - Adams, Bethany (2025)
Children with hearing loss (CHL) appear to experience greater fatigue than children with normal hearing (CNH). Listening-related fatigue is a type of fatigue often associated with an increase in effortful listening or difficult listening situations. This has been observed in children with bilateral hearing loss (CBHL) and, more recently, in children with unilateral hearing loss (CUHL). Available tools for measuring fatigue in children include general fatigue questionnaires such as the child self-report and parent-proxy versions of the PedsQLTM Multidimensional Fatigue Scale (MFS) and the PROMIS Fatigue Scale. Recently, the Vanderbilt Fatigue Scale (VFS-C: child self-report; VFS-P: parent-proxy report) was introduced with a specific focus on listening-related fatigue. Though CHL experience listening-related fatigue, it is unclear which tools are the best for measuring fatigue in this population, its mechanisms in CUHL and CBHL and how/if they differ, or the nature of the fatigue these children experience.